Navigating English as a Medium of Instruction Practices in a Public School - Mishra, Dipak (Journal of NELTA, 2024)
The Implementation of English as a Medium of Instruction (EMI) in public schools has been connected with teachers’ competence, teachers’ professional development and teacher learning processes. The study adopts the qualitative case study to explore EMI practices in a classroom of a public school through the lenses of Vygotsky’s (1978)social interactional theory. The study looks into the experiences and practices of teachers, students, and other stakeholders in EMI classrooms. The research findings show that teachers are unable to make their pedagogy meaningful as the textbooks of private publications are entirely designed for commercial purposes; as a result, the students are quiet and passive due to the fear of EMI in the classroom. The study also reveals that newly appointed teachers have a zeal to enhance professional development and network among the teacher community to uplift students’ levels. Lastly, the paper paves the way for in-depth debate on EMI policy and practices in public schools.